Analysis of the Influence of Non-Physical Work Environment and Ability on Employee Performance at PT. Central Kelolal Abadi - Grace Indah R Simanjuntak; Saimara AM Sebayang; Firmansyah (International Journal of Economics and Management, 2026)
This study aims to analyze the influence of ability and non-physical work environment on employee performance at PT. Central Kelola Abadi. The problem addressed in this study is the suboptimal employee performance, indicated by declining performance scores, differences in work quality, and delays in task completion. This research employed a quantitative approach with an associative research method. The population consisted of all employees of PT. Central Kelola Abadi, and data were collected through questionnaires. Data analysis was conducted using multiple linear regression with SPSS version 25. The results showed that ability has a positive and significant effect on employee performance, with a t-value of 5.540 and a significance level of 0.000 < 0.05. The non-physical work environment also has a positive and significant effect on employee performance, with a t-value of 14.952 and a significance level of 0.000 < 0.05. Simultaneously, ability and non-physical work environment have a positive and significant effect on employee performance, as indicated by an F-value of 666.631 and a significance level of 0.000 < 0.05. The coefficient of determination test produced an Adjusted R Square value of 0.953, indicating that ability and non-physical work environment explain 95.3% of the variation in employee performance, while the remaining 4.7% is influenced by other variables not examined in this study. Therefore, improving employee ability and creating a conducive non-physical work environment can enhance employee performance at PT. Central Kelola Abadi.